Congenital Complete Atrioventricular Block and Dilated Cardiomyopathy: New Light for an Old Disease - Mariana Paiva; Vania Ribeiro; Raquel Garcia; Sandra Amorim; Manuel Campelo; Elisabete Martins; Brenda Moura; Jose Cardoso; M. Júlia Maciel (Case Reports in Cardiology)
We present a case of a patient with known complete congenital atrioventricular block (CAVB) since the age of 7 years old that developed dilated cardiomyopathy ten years after VVI-R pacemaker implantation. He presented severe biventricular dysfunction and was symptomatic despite optimal medical therapy. Cardiac resynchronization therapy was used, and he showed clinical and electrocardiographic improvement a month later.